Vascular endothelial growth factor in gingival crevicular fluid around dental implants - Mierzwinska-Nastalska, E (Eur J Med Res, 2010)
INTRODUCTION: Angiogenesis occurs under physiological and pathological conditions and is regulated by cytokines and growth factors. Vascular endothelial growth factor (VEGF) is a multifunctional angiogenic cytokine that plays a significant role in inflammation and immune responses implicated in the pathogenesis of inflammatory processes in the implant- surrounding tissues. OBJECTIVE: The study investigated the concentration of VEGF in gingival crevicular fluid (GCF) in healthy and diseased soft tissues surrounding implants. MATERIAL AND METHODS: Clinical examinations were focused on assessing the periodontal status of soft tissues around dental implants with the use of Florida Probe. Bone loss was examined radiologically. VEGF concentrations were assessed by enzyme-linked immunoabsorbent assay (ELISA). RESULTS: VEGF concentrations were found higher in crevicular fluid around implants than in clinically healthy sites. They were also strongly correlated with the pocket depth. CONCLUSIONS: The presence of VEGF in gingival crevicular fluid in patients with peri-implants can be implicated in the progression of peri-implantitis, possibly by promoting the formation of new blood vessels during angiogenic processes.